2019
DOI: 10.3389/fimmu.2019.01237
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas salmonicida subsp. salmonicida Early Infection and Immune Response of Atlantic Cod (Gadus morhua L.) Primary Macrophages

Abstract: In contrast to other teleosts, Atlantic cod ( Gadus morhua ) has an expanded repertoire of MHC-I and TLR components, but lacks the MHC-II, the invariant chain/CD74, and CD4 + T cell response, essential for production of antibodies and prevention of bacterial infectious diseases. The mechanisms by which G. morhua fight bacterial infections are not well understood. Aeromonas salmonicida subsp. salmonicida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 72 publications
(96 reference statements)
2
32
0
Order By: Relevance
“…In summary, we found that Salmo salar erythrocytes have phagocytic capabilities (Figures ), but lower than primary macrophages (Soto‐Davila et al, ). Although the S. salar erythrocytes have the ability to phagocyte bacteria and particles (Figures ), A. salmonicida remains in a viable cultivable state in erythrocytes and blood of infected animals (Figure b).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In summary, we found that Salmo salar erythrocytes have phagocytic capabilities (Figures ), but lower than primary macrophages (Soto‐Davila et al, ). Although the S. salar erythrocytes have the ability to phagocyte bacteria and particles (Figures ), A. salmonicida remains in a viable cultivable state in erythrocytes and blood of infected animals (Figure b).…”
Section: Discussionmentioning
confidence: 51%
“…Here, using in vivo and in vitro approaches, we present evidence that A. salmonicida invades S. salar erythrocytes, which is a novel feature for furunculosis that could benefit the bacterial dispersion throughout the host tissues. Additionally, we observed that S. salar erythrocytes have a minor phagocytic activity compared to primary macrophages of Atlantic salmon and Atlantic cod (Soto‐Davila et al, ). These results are coincident with previous studies that showed that O. mykiss RBC have phagocytic activity (Passantino et al, ).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations